2020
DOI: 10.1177/0308022620949093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a pain management programme on occupational performance are influenced by gains in self-efficacy

Abstract: Introduction The perceived capacity to perform particular activities or skills (i.e. self-efficacy) is paramount in occupational therapy and is thought to be reinforced by actual functional capacity. This study examined whether changes in self-efficacy or confidence to lift weighted items influences changes in occupational performance and disability levels in patients attending a cognitive behavioural therapy pain management programme. Method Clients attending an 8-week cognitive behavioural therapy pain manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Previous studies suggest that pain self-efficacy is positively associated with adjustment to a persistent pain condition. 27 , 53 Improvements in pain self-efficacy after an intervention are expected to be reflected in reductions of pain-related disability. 1 , 15 , 18 , 53 A study by Thomas et al indicated that the effects of a pain management program on occupational performance were influenced by gains in skills and confidence, including self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggest that pain self-efficacy is positively associated with adjustment to a persistent pain condition. 27 , 53 Improvements in pain self-efficacy after an intervention are expected to be reflected in reductions of pain-related disability. 1 , 15 , 18 , 53 A study by Thomas et al indicated that the effects of a pain management program on occupational performance were influenced by gains in skills and confidence, including self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 53 Improvements in pain self-efficacy after an intervention are expected to be reflected in reductions of pain-related disability. 1 , 15 , 18 , 53 A study by Thomas et al indicated that the effects of a pain management program on occupational performance were influenced by gains in skills and confidence, including self-efficacy. 53 Pain self-efficacy beliefs (ie, confidence to function despite pain) have a stronger association with disability, pain behavior, and confidence to perform at work than with pain intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients seeking treatment for pain or mental health symptoms do so because they have persistent symptoms that are distressing or disruptive, and principally seek to reduce or ameliorate those symptoms (e.g., consistent with the precontemplation or contemplation stages of change with persistent focus on a medical cure; Gersh et al., 2011). We recognize, however, that the most effective rehabilitation psychology approaches focus on enhancing function and reducing disability (Thomas et al., 2021), and not symptom resolution per se. The present study focused on identifying patterns and predictors of reductions in both symptoms and their impacts on functioning over time.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational therapy assessments applied in the REVEAL(OT) could deliver information helpful to the other healthcare disciplines at the MPC such as weekly activity schedules or clinical reports on working with occupational goals. If occupational therapy became an integrated part of usual care, occupational therapists could assist in measuring and evaluating the treatment effect on occupational performance and satisfaction, which some evidence links to self-efficacy (Thomas et al, 2020 ). Self-efficacy is, in turn, associated with chronic pain prognosis (Martinez-Calderon et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%